DEMOKRASI PANCASILA DALAM PANDANGAN ULAMA TAFSIR DEMI MEWUJUDKAN NEGERI YANG BALDATUN THAYYIBATUN WA RABBUN GHAFUR - Didik Darmadi (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Democracy is often considered as a polemic system and it’s antagonized against Islam because it comes from West, even though in fact many Islamic countries have adopted it as a state system. This research aims to determine the position of democracy in Tafsir Al-Qur’an perspective as the main source of Islamic Law, spesifically Pancasila Democracy which has been implemented in Indonesia. This research is library research with comparative analysis method (al-tafsi>r al-muqa>ran) on the interpretation of Sayyid Qutb, Muhammad Rasyid Ridha, and Muhammad Mahmud Al-Hijazi. From the results of the comparison is known that democracy is different from the concept of shura, but both have similarities in terms of being anti-authoritarian and dictatorial leadership. Democracy can also be adapted in Islamic country on the condition that it must be religious and provide space for the formalization of religious rules and legislation as applicable in the Pancasila democratic system. Therefore, muslim peoples must play an active role in it to keep Indonesia as religious democratic country and become a Baldatun Thayyibatun wa Rabbun Ghafu>r country.